Transport of Methylmercury through the Epithelial Type Amino Acid Transporter System B0 (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: System B0 is a sodium dependent transporter that transports wide variety of neutral amino acids in the intestinal and renal proximal tubular epithelial cells. Methylmercury (MeHg) readily and non-enzymatically reacts with cysteine to form conjugate structurally similar to the amino acid methionine.Objective: In this study, we investigated the molecular mechanism of absorptive transport of MeHg in intestine using Xenopus oocytes expressing hB0AT1 and the uptake of metylmercry-Cys (MeHg-Cys) by heterodimeric amino acids transporter.Methodology: We confirmed the uptake of [14C] L-Leucine a potent substrate for the hB0AT1 amino acids transporter. The uptake of [14C] L-leucine by hB0AT1 was inhibited by MeHg-Cys conjugate, leucine, cysteine, methinine and phenylalanine in concentration–dependent manner. The IC50 of MeHg-Cys conjugate was significantly lower than that of leucine, cysteine, methinine and phenylalanine, indicating that hB0AT1 is a high affinity MeHg transporter. To assess MeHg-Cys conjugate transport, we measured [14C] MeHg uptake in Xenopus oocytes expressing hB0AT1 in presence or absence of sodium. The [14C] MeHg was transport only in the presence of cysteine and the transport was significantly sodium dependent and inhibited by a system B0 inhibitor 2-aminobicyclo-[2,21]- haptane-2-carboxylic acid (BCH).Result: The current findings indicate that hB0AT1 and heterodimeric amino acids absorb MeHg in the form of cysteine conjugate from the intestinal lumen across the brush-border membrane in to the cells and is supposed to be plays a critical role in the pathogenesis of Minamata disease and present results descried a major molecular mechanism by which MeHg is transported across cell membranes and indicate that metal complexes may form a novel class of substrates for amino acid carriers.Conclusion: In this experiment the results also suggest that uptake of Methionine and MeHg-Cys by heterodimeric amino acid transporter is significantly correlated where the uptake of Methionine and MeHg-Cys between heterodimeric amino acid transporter and hB0AT1 is not correlated.Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 127-136